The dynamical behaviour of structures - Warburton, Geoffrey Barratt, 1924- (Pergamon international library of science, technology, engineering, and social studies., 1976)
The Dynamical Behaviour of Structures explores several developments made in the field of structural dynamics. The text provides innovative means to identify the effect of earthquakes on buildings of various types. The mathematical aspect of beam vibrations is discussed in detail, and the different types of vibrations are also explained.